2010
DOI: 10.1080/07448481.2010.486811
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis B Surface Antigen in US-Born and Foreign-Born Asian/Pacific Islander College Students

Abstract: The prevalence of chronic hepatitis B (HBV) among college-age US-born Asian and Pacific Islanders (A/PI) is not well known. OBJECTIVES To compare the prevalence of hepatitis B surface antigen (HBsAg) seropositivity in US-born to A/PI-born students at a public university. PARTICIPANTS Undergraduate who self-identified themselves as A/PI. RESULTS Of 145 US-born A/PI, 1.4% (C.I. = 0.0%, 3.3%) tested positive for HBsAg compared to 3.3% (C.I. = 0.5%, 6.1%) of the 152 A/PI-born students. Approximately 1/3 of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…[1718192021222326] Knowledge about transmission routes of HBV was especially low, with only 13% of Korean college students correctly answering that HBV is not genetic — A finding that is significantly lower than the 44%-52% found in Lee and colleagues’ study. [17] Lee and others concluded that familial clustering of HBV infection may have been perceived as genetic factors or as an inheritance pattern in families in this ethnic group.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…[1718192021222326] Knowledge about transmission routes of HBV was especially low, with only 13% of Korean college students correctly answering that HBV is not genetic — A finding that is significantly lower than the 44%-52% found in Lee and colleagues’ study. [17] Lee and others concluded that familial clustering of HBV infection may have been perceived as genetic factors or as an inheritance pattern in families in this ethnic group.…”
Section: Discussionmentioning
confidence: 93%
“…In other studies, lower levels of knowledge about HBV infection among Asian American immigrant populations have been found to be impacted by low education as well as poor English language proficiency and ineffective communication with health care providers and health care educators. [271718192021222326] Compared with immigrant adults in community settings, college students without language barriers were assumed to have increased access to medicine, information and knowledge. However, we found that higher education and English proficiency were not predictors of HBV knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation